Laju Pertumbuhan Intrinsik dan Neraca Hidup Wereng Cokelat pada Tanaman Padi Akibat Perubahan Iklim Global - E., Baehaki S.; Iswanto, Eko Hari; Munawar, Dede (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Study on the intrinsic growth rate of natural increases of brown planthopper (BPH) was carried out in Sukamandi, Subang, West Java in 2012 at the screen house of Indonesian Center for Rice Research using host of two rice varieties, Pelita I/1 and Inpari 13. The study evaluated the effects of global climate changes on the development of brown planthopper after three decades since the first study in 1984. Results showed that the development of brown planthopper in Sukamandi, Subang field after a period of three decades was very different from the brown planthopper in 1984. The intrinsic rate of natural increase of BPH on Pelita I/1 was rm= 0.2285 wich was 2.22 fold in three decades and on Inpari 13 variety was rm = 0.2209 or 2.14 folds compared to that in 1984. Generation time of BPH on Pelita I/1 and on Inpari 13 was shorter by 0.81-0.83 times. The index of BPH survival on Pelita I/1 reached 5.2299 times and the index of the BPH survival on Inpari 13 reached 5.8881 times, compared to that of three decades ago. BPH development on Pelita I/1 showed that the ratio of females: males was 74%: 26%. In Inpari 13 variety showed the ratio females: males was 70.8%: 29.2%. Based on the description, the intrinsic growth rate of natural increases of brown planthopper had changed over three decades. The implications was that the population dynamics of brown planthopper had changed toward higher fitness as affected by global climate change.